Hubungan Antara Kadar Vascular Cell Adhesion Molecule-1 (VCAM-1) Dan Riwayat Berat Badan Lahir Rendah Pada Anak Usia 15-18 Tahun - Santoso, Mas Nugroho Ardi (Jurnal Kedokteran Indonesia, 2009)
Background: Children with history of low birth weight have the risk of atherosclerosis in their future.Vascular cell adhesion molecule-1 (VCAM-1) is a group of immunoglobulin adhesion molecules, a receptorprotein to marginalization process and mononuclear leukocytes movement along the endotholium.VCAM-1 is an early marker of atherosclerosis which can be detected at an early age. This study aimedto analyze the relationship between levels of VCAM-1 and history of low birth weight among childrenaged 15-18 years old.Methods: A historical cohort study was conducted to senior high school students in Surakarta in July2010. A Sample of students aged 15-18 years were selected by fixed exposure sampling. The data wereanalyzed by Mann-Whitney test and multiple linear regression analysis.Results: Of 700 students, 9 students had a history of low birth weight. With the 1:3 ratio obtained, thetotal study subjects were 28. Children with history of low birth weight had VCAM-1 mean level of 224.6ng / ml higher than those with normal birth weight (b = 224.6, p <0.001), after controlling for obesity.Conclusion: VCAM-I is associated with history of low birth weight. Children with history of low birthweight have higher VCAM-1 mean levels than those of normal birth weightKeywords: VCAM-1, children, history of low birth weight